Top speed sprinting: Thigh angular motion and eccentric hamstring strength in faster vs. slower sprinters - Alt, T.; Komnik, I.; Ryan, L. J.; Clark, K. P. (Human Movement Science, 2024)
Sprinting at maximum velocity requires fast angular motion of the thigh and effective hamstring function for optimum performance and injury prevention. In this cross-sectional investigation of 21 male sprinters, we acquired thigh angular kinematics while sprinting at top speed (range: 8.96-10.17 m/s), and then measured eccentric hamstring strength capacities using an isokinetic dynamometer during the same test session. In agreement with the hypotheses, thigh angular motion rates and the associated eccentric hamstring strength capacities were both significantly correlated with top speed (r-values: ~0.5; p < 0.05). Additionally, when the participants were sorted by top speed, there were significant differences between the faster group and the slower group. Notably, on average the faster group showed faster thigh motion (angular acceleration: 10.3 kdeg/s2, 11 % greater than slower group) and higher eccentric hamstring strength capacities (peak moment: 2.26 Nm/kg, 14 % greater than slower group). This investigation indicates that fast thigh angular motion and eccentric hamstring strength are both important for sprint performance.